An effective strategy to realize superior high-temperature energy storage properties in Na0.5Bi0.5TiO3 based lead-free ceramics. Issue 18 (15th September 2021) - Huang, Jie; Fan, Zhenhao; Gao, Shuaibing; Zhang, Qingfeng; Lu, Yinmei; He, Yunbin
Abstract: To develop and fabricate environmentally friendly dielectric capacitors used in high-temperature environment, in this work, we prepare La 3+ doped 0.94Na0.5 Bi0.5 TiO3 -0.06BaTiO3 lead-free relaxor ferroelectric ceramics with high and wide phase transition temperature. With the introduction of La 3+, due to the enhancement of the A- and B- site cation ion disorder, the dielectric relaxation characteristics of the ceramics are more obvious. Therefore, the polarization-electric field loops become slimmer and the remnant polarization ( P r ) reduces. In addition, because La 3+ as a donor dopant has lower mobility than A-site cation ions in the ceramic matrix, the grain sizes decrease with increasing La 3+ content, which significantly leads to an increase in the breakdown strength ( E b ). As a result, both a large recoverable energy density ( W rec ) of 1.92 J/cm 3 and a high energy efficiency ( η ) of 85.7% are obtained in the ceramic with 12 mol% La 3+ content. More importantly, even at 200 °C and a low driving electric field of 155 kV/cm, the W rec and η of this kind of ceramic are still as high as 1.2 J/cm 3 and 89.4%, indicating good temperature stability. This work provides an effective and simple way to prepare environmentally friendly dielectric capacitors that are applicable in high-temperature environment.